Pengaruh Penerapan Model Problem Based Learning Terhadap Disposisi Matematis Mahasiswa Teknik Sipil - Windry Novalia Jufri; Neviyarni Neviyarni (Jurnal Ilmiah Wahana Pendidikan, 2020)
This study intended to analyze whether the mathematical disposition of students who got problem-based learning was better than students who got conventional learning. This research was conducted by using a quasi-experimental research with a posttest only group design. The students of civil engineering 2018 who took the calculus course were involved as the participants of this research. Regarding to the selected research design, sample selection was done by drawing the participants’ classes. One of the selected classes was used as the experimental class and the other class was used as the control class. The experimental class was given treatment with a problem based learning model while the control class was given treatment with conventional learning models. Based on the results of data analysis, it was found that sig. (1-tailed) was equal to 0.0005 <α = 0.05, so that Ho was rejected. Therefore, it can be concluded that the mathematical disposition of the experimental class students was significantly better than the mathematical disposition of the control class students